2004
DOI: 10.4269/ajtmh.2004.70.591
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Pyrethroid Knockdown Resistance Allele in Western Kenyan Populations of Anopheles Gambiae in Response to Insecticide-Treated Bed Net Trials

Abstract: Permethrin and DDT resistance in Anopheles gambiae s.s. associated with a leucine-serine knockdown resistance (kdr) mutation in the voltage-gated sodium channel gene was discovered recently in western Kenya where a large scale permethrin-impregnated bed net (ITN) program has been implemented. Collections of An. gambiae s.l. were made from intervention and control villages prior to and after onset of the program. The kdr genotypes were determined using allele-specific polymerase chain reaction diagnostic tests.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
168
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(179 citation statements)
references
References 40 publications
10
168
1
Order By: Relevance
“…Since no any other sibling species apart from Anopheles arabiensis was identified by molecular means, it is unlikely that any of the failed amplifications would identify to any other sibling species. In previous studies from the same region A. arabiensis mosquitoes were found to be the only sibling species of A. gambiae complex mosquitoes [33,34,31]. In a study carried out at Mwea rice irrigation scheme, A. arabiensis mosquitoes were found to be the only member of A. gambiae complex mosquitoes [35].…”
Section: Discussionmentioning
confidence: 99%
“…Since no any other sibling species apart from Anopheles arabiensis was identified by molecular means, it is unlikely that any of the failed amplifications would identify to any other sibling species. In previous studies from the same region A. arabiensis mosquitoes were found to be the only sibling species of A. gambiae complex mosquitoes [33,34,31]. In a study carried out at Mwea rice irrigation scheme, A. arabiensis mosquitoes were found to be the only member of A. gambiae complex mosquitoes [35].…”
Section: Discussionmentioning
confidence: 99%
“…Our survey found that occasional agricultural insecticide use in Kenya was primarily in the rice, coffee/tea plantation and sugar cane growing areas while other areas reported little use of insecticides . Stump et al (2004) reported that the frequency of the kdr allele in An. gambiae increased from 3-4% to 4-8% after 7-8 years of using pyrethroid-treated bednets in an ITN trial area in Asembo Bay, west Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…Permethrin knock-down resistance has arisen independently at least twice in Africa. In west Africa, kdr was caused by a leucine-phenylalanine substitution at position 1014 of the sodium channel gene (L1014F) whereas a different mutation (leucine-serine substitution) at the same amino acid position (L1014S) was associated with kdr resistance in Kenya in both A. gambiae and A. arabiensis (Martinez-Torres et al 1998;Ranson et al 2000;Stump et al 2004). However, the L1014F mutation has been detected in An.…”
Section: Introductionmentioning
confidence: 99%
“…Both mutations have also been reported to co-exist in Gabon and Cameroon [106] and in Uganda [107]. The western kdr was also detected in Kenya [108], Tanzania [109], and also in Zambia [110,111]. In pyrethroid-resistant An.…”
Section: Distribution Of Insecticide Resistancementioning
confidence: 99%